Effect of main chain modification during reversion on strain‐induced crystallization of polyisoprene rubbers. Issue 5 (11th March 2022) - Lin, Feifei; Jia, Weijie; Zhong, Liang; Liu, Feng; Zhang, Hao; Wang, Bin; Song, Yudian
Abstract: The effect of main chain modification during reversion on strain‐induced crystallization (SIC) of unfilled natural rubber (NR) and synthetic polyisoprene rubber (IR) cured with a conventional vulcanization system has been investigated. To eliminate the interference of crosslink density, vulcanizates were prepared using different amounts of curatives, chosen to give mainly monosulfidic or carbon–carbon crosslinks, having similar crosslink densities to the conventional compound at different states of reversion. Crystallinity was characterized by the degree of stress softening, and the contents of trans ‐methine were qualitatively and quantitatively analyzed by Fourier transform infrared spectroscopy. It was found that crosslink density exerts much greater influence on crystallinity than crosslink structure. At the same crosslink density, SIC of NR vulcanizates after reversion is lower than that of samples cured with tetramethylthiuram disulfide or dicumyl peroxid to the optimum cure state, which might be attributed to molecular main chain modification during reversion. NR was found to have better reversion resistance than IR. Abstract : Crosslink density exerts much greater influence on crystallinity than crosslink structure. At the same crosslink density, SIC of NR vulcanizates after reversion is lower than that of samples cured with TMTD or DCP to the optimum cure state, which might be attributed to molecular main chain modification during reversion. NR was found to have better reversion resistance than IR.